MAKNA TAYANGAN INDONESIA LAWYERS CLUB DI TVONE (WACANA KRITIS MENGENAI KETERLIBATAN ANAS URBANINGRUM DALAM KORUPSI HAMBALANG) - Mayasari Mayasari; Andi Alimuddin Unde; Muhammad Iqbal Sultan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2015)
Abstract Development of the mass media have impact in the history of human life. The Study aims to determine the representation of the discourse on Anas Urbaningrum shown through the texts that are present in the interaction process during Indonesia Lawyers Club program lasted six episodes that discuss topics related to corruption cases involving Anas Urbaningrum.This study used a qualitative research approach. Qualitative Methods in Critical Discourse Analysis of Social Cognition models used to analyze representations of discourse and text about the production process in the event program Anas Urbaningrum Indonesia Lawyers Club.The results of this study indicate that the six episodes of